Therapeutic effects of a novel BAFF blocker on arthritis - Zhou, Bailing (Signal Transduct Target Ther, 2019)
B-cell targeted therapy is effective for autoimmune diseases such as systemic lupus erythematosus and rheumatoid arthritis (RA), although there are setbacks in RA clinical trials. In this study, we designed a novel B-cell activating factor (BAFF) antagonist: BAFF-Trap, a recombinant glycoprotein with BAFF-binding domains of two BAFF receptors (TACI and Br3) linked to Fc domain of human IgG1. Unlike TACI-Fc, BAFF-Trap bound BAFF but not APRIL (a proliferation-inducing ligand), and significantly suppressed the development of collagen-induced arthritis and adjuvant-induced arthritis. Furthermore, BAFF-Trap inhibited proinflammatory cytokine expression, ameliorated joint damage and suppressed B- and T-cell activation. BAFF-Trap reduced dendritic cells in joints, and increased regulatory T cell, regulatory B-cell, and M2 macrophage. The function of BAFF-Trap was related to inhibition of canonical and noncanonical NF-κB activation. Thus, BAFF-Trap may be a valuable agent for the effective treatment of RA.